2021
DOI: 10.3390/ma14164665
|View full text |Cite
|
Sign up to set email alerts
|

Wear-Resistant TiC Strengthening CoCrNi-Based High-Entropy Alloy Composite

Abstract: In order to improve the wear resistance of CoCrNi alloy, TiC was introduced into the alloy and wear-resistant CoCrNi/(TiC)x composites were designed. The effects of TiC contents on the microstructure, mechanical properties, and wear resistance of CoCrNi matrix were investigated, respectively. It was found that the TiC produced dissolution and precipitation process in CoCrNi alloy, and a large number of needled and blocky TiC particles were precipitated in the composites. The compressive yield strength of CoCrN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Co, Cr, and Ni are all present as single crystal structures in the hybrid powders. And as can be seen from Figure 3, the laser cladding caused the CoCrNi ternary alloy to form a single-phase face-centered cubic solid solution, and the phase of the TCB0 coating consists of a single FCC phase, which agrees with the previous reports [31,32], indicating that the high entropy effect of the multi-major elemental CoCrNi coatings inhibited the formation of intermetallic compounds. When TiC and TiB2 were added, the coating phase changed but retained the single-phase FCC structure of CoCrNi, which transformed from a single FCC phase to a multi-phase of FCC + TiC + TiB2 without forming other phases.…”
Section: Phase Compositionsupporting
confidence: 88%
“…Co, Cr, and Ni are all present as single crystal structures in the hybrid powders. And as can be seen from Figure 3, the laser cladding caused the CoCrNi ternary alloy to form a single-phase face-centered cubic solid solution, and the phase of the TCB0 coating consists of a single FCC phase, which agrees with the previous reports [31,32], indicating that the high entropy effect of the multi-major elemental CoCrNi coatings inhibited the formation of intermetallic compounds. When TiC and TiB2 were added, the coating phase changed but retained the single-phase FCC structure of CoCrNi, which transformed from a single FCC phase to a multi-phase of FCC + TiC + TiB2 without forming other phases.…”
Section: Phase Compositionsupporting
confidence: 88%
“…The results showed that the microhardness of the composite coatings was high at the surface and low at the bottom, which was similar to the gradient distribution of TiC-reinforced particles. Cai et al [10] designed wear-resistant CoCrNi/(TiC)x composites by introducing TiC into the alloy to improve the wear resistance of CoCrNi alloy. It was found that the compressive yield strength of the CoCrNi/(TiC)x composites increased with the increase of TiC content.…”
Section: Introductionmentioning
confidence: 99%